Searching for remote homologs of CAML among eukaryotes. (3rd September 2020) - Borgese, Nica
Abstract: The tryptophan rich basic protein/calcium signal‐modulating cyclophilin ligand (WRB/CAML) and Get1p/Get2p complexes, in vertebrates and yeast, respectively, mediate the final step of tail‐anchored protein insertion into the endoplasmic reticulum membrane via the Get pathway. While WRB appears to exist in all eukaryotes, CAML homologs were previously recognized only among chordates, raising the question as to how CAML's function is performed in other phyla. Furthermore, whereas WRB was recognized as the metazoan homolog of Get1, CAML and Get2, although functionally equivalent, were not considered to be homologous. CAML contains an N‐terminal basic, TRC40/Get3‐interacting, region, three transmembrane segments near the C‐terminus, and a poorly conserved region between these domains. Here, I searched the NCBI protein database for remote CAML homologs in all eukaryotes, using position‐specific iterated‐basic local alignment search tool, with the C‐terminal, the N‐terminal or the full‐length sequence of human CAML as query. The N‐terminal basic region and full‐length CAML retrieved homologs among metazoa, plants and fungi. In the latter group several hits were annotated as GET2. The C‐terminal query did not return entries outside of the animal kingdom, but did retrieve over one hundred invertebrate metazoan CAML‐like proteins, which all conserved the N‐terminal TRC40‐binding domain. The results indicate that CAML homologs exist throughout the eukaryotic domain of life, and suggest that metazoan CAML and yeast GET2 share a common evolutionary origin. They further reveal a tight link between the particular features of the metazoan membrane‐anchoring domain and the TRC40‐interacting region. The list of sequences presented here should provide a useful resource for future studies addressing structure‐function relationships in CAML proteins. Abstract : The CAML/WRB and Get1p/Get2p complexes, in vertebrates and yeast, respectively, mediate integration of tail‐anchored proteins into the Endoplasmic Reticulum membrane. While WRB homologs exist in distantly related phyla, previous investigations revealed CAML only among vertebrates. The bioinformatic search for remote CAML homologs, reported here, returned sequences also in distantly related groups, including plants and fungi, where several hits were annotated as GET2. Thus, CAML and GET2 likely share a common evolutionary origin, and operate throughout the eukaryotic domain of life.